Pengaruh Minat Berwirausaha Dan Penggunaan Sosial Media Terhadap Kewirausahaan Mahasiswa UINSU Medan - Lanny Suryani Siregar; Sindi Pratiwi; Widya Sari Nasution; Mansur Keling (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
Interest in entrepreneurship can be seen from the willingness to work hard and diligently to achieve progress in one's business, the willingness to bear various risks related to the business actions one undertakes, the willingness to take new paths and methods, the willingness to live frugally, the willingness to learn from what one has experienced. In this research, researchers used qualitative methods. The data collection method is a questionnaire and several related literature. Meanwhile, the population in this study were students at the North Sumatra State Islamic University, Medan. The aim of this research was to determine the influence of interest in entrepreneurship and use of social media on student entrepreneurship.